Government Collaboration in Developing Creative Skills to Realize the Empowerment of Mental Patients - Fatriani, Riri Maria; Febrianti, Rima Sukma; Al-Amiirah, Syafiiqah (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Government plays an important role in creating an environment that supports the development of creative skills for mental patients, which contributes to increased sense of empowerment, better self-confidence, and positive social interaction. This study analyzes how this collaboration between stakeholders empowers mental patients in the form of creativity skills in Indonesia. This research uses a qualitative approach The source of this research data is Online news media. Data is obtained using the N capture feature on Nvivo 12 plus where the N capture feature is a web browser extension developed to capture web content in the form of website content, social media, and other document content such as scientific articles. The results showed that the government has an important role in the implementation of empowerment, which is as much as 42.39%, then mental hospitals contribute as much as 33.77%, and finally creative industry players who conduct skills training as much as 24.83%. From this data, it shows that these three related elements have provided real implementation for mental patients so that justice and patient rights can be fulfilled. The skills provided consist of Visual Arts, Music and Music Therapy, Creative Writing, Garden and Landscaping, Handicrafts.